An improved multiple-aliquot regenerative-dose (MAR) procedure for post-IR IRSL dating of K-feldspar - Li, B.; Jacobs, Z.; Roberts, R. G. (Ancient TL, 2017)
In optical dating, multiple-aliquot dating methods have been considered inferior to single-aliquot methods, due to difficulties inherent to in between-aliquot normalisation. In this study, we propose an improved multiple-aliquot regenerative-dose (MAR) procedure for the multiple-elevated-temperature post-IR IRSL (MET-pIRIR) signals from K-feldspar grains. This method is based on observations that a common, or standardised, growth curve (SGC) exists between different aliquots from the same and different samples, and that between-aliquot variation can be largely eliminated by application of regenerative-dose (’re-normalisation’) or least squares (LS) normalisation procedures. We find that this improved MAR procedure significantly increases the accuracy and precision of De determinations. We tested this method using several sediment samples from Marathousa, a Middle Pleistocene archaeological site in Greece, and demonstrate that, for the K-feldspar grains from these samples, the proposed MAR method overcomes problems associated with inappropriate sensitivity correction of the natural (Ln) and test dose (Tn) signals at low stimulation temperatures (50 – 150 ◦C) more effectively than the SAR method. The MAR method can also reduce instrument time for measurement of older samples.